Transaktionen und Servicing in der Finanzkrise: Berichte und Referate des Frankfurt School NPL Forums 2008 - Christoph Schalast; Markus Bolder; Claus Radünz; Stephanie Siepmann; Thorsten Weber (Frankfurt School of Finance & Management, 2009)
The report describes the current developments of the German market for Non Performing Loans/Distressed Debt as it is influenced by the financial crisis/credit crunch. Furthermore the sale of (small and medium sized) real estate portfolios since summer 2007 is analysed in more detail.
urn:nbn:de:101:1-2009042215
Keywords: K12; K19; K22; K29; 330; Non performing loans; distressed debt; portfolio management; workout; outsourcing; servicing; banking and regulation law; bankers duty of secrecy; failing banks; corporate loans; consumer loans; real estate loans; Notleidende Kredite; Kreditmarkt; Wertpapierhandel; Portfolio-Management; Realkredit; Finanzmarktkrise; Deutschland